Papua dan Panggilan Macedonia di Zaman Milenium Baru - Fransiskus Irwan Widjaja (DIEGESIS: Jurnal Teologi Kharismatika, 2019)
Mission is an integral part of Christianity. The activities of the western world mission that have sent 164 years of missionaries to the land of Papua have no impact on Papua. The existence of the church of God in the land of Papua also has no impact and significance for the people of Papua. Papua lost its identity as a gospel land. The high level of Islamization, the low level of education, and the high level of poverty makes it necessary for Papua to be helped. Papua is calling as Macedonia calls in the millennium. AbstrakMisi merupakan bagian yang integral dengan agama Kristen. Kegiatan misi dunia barat yang sudah mengutus misionari 164 tahun ke tanah  Papua, tidak membaw dampak bagi Papua Keberadaan gereja Tuhan di tanah papua juga tidak membawa dampak dan berarti bagi penduduk papua. Papua kehilangan jati diri sebagai tanah injil. Tingginya islamisasi, rendahnya tingkat pendidikan dan tingginya kemiskinan membuat papua perlu di tolong. Papua sedang memanggil seperti Panggilan Macedonia di jaman millennium.